Integrasi Metode RCA dan TRIZ dalam Menyelesaikan Masalah Produksi Bata Ringan (Studi Kasus di PT. X) - Almuhari, Hanif Jibran; Jazuli, Jazuli (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This research was conducted at PT X which experienced non-achievement of production targets during the period November 2023 to February 2024. The purpose of the research is to identify the root causes of target non-achievement and design solutions. The method used is Root Cause Analysis (RCA) with Fishbone Diagram and 5 Whys Analysis tools, to evaluate the causes of various aspects of production. The data analyzed included production data and machine breakdown data during the period. The analysis found 15 root causes originating from four main aspects, namely machines, people, methods, and materials. The machine factor was the dominant cause with a contribution of 40%. To formulate a solution, the TRIZ (Theory of Inventive Problem Solving) approach was used, which offers a systematic and innovative way. TRIZ derives 14 principles that emphasize the importance of adaptive and predictive systems to prevent errors in the first place, rather than adding resources. The integration of RCA and TRIZ proved effective in generating comprehensive solutions to complex production problems.